Assessment of auxotrophic sanitary-indicative microorganisms occurrence in radiation-contaminated soils - Sysa, Aliaksei; Maltseva, Svetlana; Butchenkov, Igor; Gritskevitch, Evgeniy; Birg, Vladimir; Ahmed, Ahmed H. D. (Journal of the Belarusian State University. Ecology, 2024)
Long-term exposure of opportunistic microorganisms to ionizing radiation can lead to an increase in the frequency of occurrence of auxotrophic variants, changes in some physiological and biochemical properties, as well as changes in nutritional needs as a result of disruption of the synthesis and functioning of specific enzymes. The purpose of the study is to assess the occurrence of auxotrophic variants of opportunistic microorganisms exposed to long-term exposure to ionizing radiation. The objects for research were pure cultures of coliform bacteria (CB), as well as the genus Bacillus, isolated from soil samples under long-term exposure to ionizing radiation. The subject of the study is to assess the occurrence of auxotrophic variants of opportunistic microorganisms. It was established that auxotrophic variants of microorganisms are found in all examined soils. There was a dependence of occurrenceundefined auxotrophs on the level of radiation contamination of soils. In soils experiencing intense radionuclide load, most isolates had multiple auxotrophy. When cultivating isolated bacterial isolates, auxotrophic variants were found for almost all analyzed amino acids. It was shown that the isolated variants of coliforms and the genus Bacillus generally differ in their requirements for individual amino acids depending on the territory from which soil samples were taken for analysis. Moreover, this difference is largely due to differentiated indicators of auxotrophy of B. mycoides.